Himpunan Fatwa keuangan syariah : Dewan syariah Nasional MUI / Tim penyunting H.M. Ichwan Sam..[et al] ; editor, Hijrah Saputra, Andriansyah Syihabuddin, Adhika Prasetya K. - Ichwan Sam, H.M.; Hijrah Saputra; Andriansyah Syihabuddin; Adhika Prasetya K. (Erlangga, 2014)
XXV, 928 hlm. ; 23 cm.